Beyond Blair: governmental politics, perceptions, and the British decision to invade Iraq - Eason, Thomas (2023)
This thesis has two aims: i) to create a new Foreign Policy Analysis (FPA) framework that analysts can use to develop detailed narratives that explain foreign policy decisions with reference to both the formation of individual perceptions as well as the role of broader bureaucratic processes in policymaking; and ii) to develop one of the most detailed academic accounts of the British decision to invade Iraq in 2003 which, using the new framework, decentres the Prime Minister and shines a new light on how previously overlooked actors and bureaucratic structures shaped the UK’s path to war. Drawing upon memoirs, declassified government documents, and testimonies made to the Iraq Inquiry, this thesis develops its new FPA framework, coined the Politics and Perceptions Framework, and tests and demonstrates it by applying it to the British decision to invade Iraq in 2003.